Os efeitos do exoesqueleto flexível baseado no conceito de tensegridade na estabilidade postural de crianças com paralisia cerebral - Emmanuelle Bozzi Rodriguez (2015)
Children with CP have disorders in postural stability. The use of appropriate elastic garments may assist in postural stability to increase, the elastic stiffness of the musculoskeletal system, without restricting mobility and postural adjustments. This study evaluated the effects of an elastic garment (Flexible Exoskeleton based on the concept of tensegrity – ExT) on the behavior and postural stability of children with typical development (TD) and CP to investigate whether children exploit the mechanical properties provided by the use of ExT. The aim was to compare the postural stability of children with CP and with typical development (TD) in the conditions with and without the use of ExT in order to assess whether its use: (1) changes the postural sway of these children as expected; (2) promotes a more deterministic oscillatory behavior in children, in static and post-perturbation conditions. Thr study also aimed (3) identifying whether changes in postural stability resulting from ExT use would be different in children with CP and TD. Twenty participants (10 hemiplegic and 10 with TD) were asked to stand up on a force platform in two conditions (static and before a perturbation) in the conditions with and without the ExT. The positions of the center of pressure (COP) were measured. Variables related to postural stability and to the expected effects of using the exoskeleton were calculated. The use of Ext led to an increased recurrence (p = 0,048) and amplitude of displacement (p = 0,018) of the COP. In children with TD, using the Ext caused increases in total displacement (p = 0,005) and velocity of displacement (p = 0,005) of the COP. The effects found were according to expected, more apparent to children with TD, except for the increase in amplitude of displacement of COP. The results showed that the mechanical properties of the ExT were used by children for maintaining postural stability. The increase in the amplitude of the COP, without increasing the average deviation of the COP from its central position, suggests that the increased amplitude was related to momentary increases in COP displacement peaks. These momentary effects may be related to a learning process, still in progress, to deal with higher speeds of displacement, though the average deviation of the COP from its central position has tended to decrease (p = 0,055). Thus, the increase amplitude indicates that there were no restrictions to the mobility needed for momentary postural adjustments of greater magnitudes. The largest number of effects for children with TD suggests that children with CP have greater difficulty in learning to take advantage of the features offered by the ExT. It can be concluded that children, especially those with TD, exploit the ExT to maintain postural stability, with further exploration of COP oscillation – highest peaks of distances, higher total trajectories and faster sways –, no increase of the average distance of the COP from its central position and production of a more recurrent COP behavior in time and space (as expected from a pendulum-elastic system to which elastic bands are added).